Corinth in context: comparative studies on religion and society - Friesen, Steven J.; Schowalter, Daniel N.; Walters, James C. (Supplements to Novum Testamentum, 2010)
Context, comparison /Steven J. Friesen --The social and ethnic origins of the colonists in early Roman Corinth /Benjamin W. Millis --Asklepios in Greek and Roman Corinth /Bronwen L. Wickkiser --The emperor in a Roman town : the base of the Augustales in the forum at Corinth /Margaret L. Laird --Greek heritage in Roman Corinth and Ephesos : hybrid identities and strategies of display in the material record of traditional Mediterranean religions /Christine M. Thomas --Image and cult : the coinage of Roman Corinth /Mary E. Hoskins Walbank --Ceres and cultural complexity : divine personality definitions and human worshippers in Roman Corinth /Jorunn Økland --The wrong Erastus : ideology, archaeology, and exegesis /Steven J. Friesen --Where have all the names gone? The Christian community in Corinth in the late Roman and early Byzantine eras /Michael B. Walbank --Seeking shelter in Roman Corinth : archaeology and the placement of Paul's communities /Daniel N. Schowalter --Paul and the politics of meals in Roman Corinth /James C. Walters --The sacred spring : landscape and traditions /Guy D.R. Sanders --Religion and society at Roman Kenchreai /Joseph L. Rife --Religion and society in the Roman Eastern Corinthia /Timothy E. Gregory.